2004
DOI: 10.5194/acp-4-2181-2004
|View full text |Cite
|
Sign up to set email alerts
|

Ozone loss and chlorine activation in the Arctic winters 1991-2003 derived with the tracer-tracer correlations

Abstract: Abstract. Chemical ozone loss in the Arctic stratosphere was investigated for the twelve years between 1991 and 2003 employing the ozone-tracer correlation method. For this method, the change in the relation between ozone and a longlived tracer is considered for all twelve years over the lifetime of the polar vortex to calculate chemical ozone loss. Both the accumulated local ozone loss in the lower stratosphere and the column ozone loss were derived consistently, mainly on the basis of HALOE satellite observa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
187
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(204 citation statements)
references
References 61 publications
15
187
2
Order By: Relevance
“…In the absence of mixing, correlations between a long-lived tracer and ozone provide a quantitative measure of chemical O 3 change [Müller et al, 2001[Müller et al, , 2005. TRAC has been successfully used to quantify chemical O 3 loss for the past decade of Arctic [Tilmes et al, 2004] Harris et al [2002] showed general agreement of TRAC-derived O 3 loss with O 3 loss derived from Lagrangian trajectory [Manney et al, 1995], vortex average [Knudsen et al, 1998], SAOZ [Goutail et al, 1999] and Match [von der Gathen et al, 1995] calculations.…”
Section: Data and Analysismentioning
confidence: 89%
“…In the absence of mixing, correlations between a long-lived tracer and ozone provide a quantitative measure of chemical O 3 change [Müller et al, 2001[Müller et al, , 2005. TRAC has been successfully used to quantify chemical O 3 loss for the past decade of Arctic [Tilmes et al, 2004] Harris et al [2002] showed general agreement of TRAC-derived O 3 loss with O 3 loss derived from Lagrangian trajectory [Manney et al, 1995], vortex average [Knudsen et al, 1998], SAOZ [Goutail et al, 1999] and Match [von der Gathen et al, 1995] calculations.…”
Section: Data and Analysismentioning
confidence: 89%
“…Chemical ozone loss in the polar regions is strongly related to the geographical extent of PSCs during the winter (e.g., Rex et al, 1999Rex et al, , 2004Rex et al, , 2006Tilmes et al, 2004). To date, realistic measurement-based estimates of PSC areal coverage have not been feasible due in large part to the limited sampling pattern of solar occultation instruments.…”
Section: Psc Processing Diagnosticsmentioning
confidence: 99%
“…In particular, as (in the absence of halogen-catalysed chemical loss) ozone in the winter polar vortex can be considered long-lived (e.g., Proffitt et al, 1992;Sankey and Shepherd, 2003), compact ozone-tracer relations are expected for the polar vortex (e.g., Proffitt et al, 1993;Müller et al, 2001;Tilmes et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Measurements from aircraft (Proffitt et al, 1990(Proffitt et al, , 1993Richard et al, 2001;Ross et al, 2004;Ulanovskii et al, 2004), satellites (Müller et al, 1996;Tilmes et al, 2003bTilmes et al, , 2004, balloons (Müller et al, 2001;Salawitch et al, 2002;Vogel et al, 2003;Robinson et al, 2005), and from the Space Shuttle (Michelsen et al, 1998) were used for such analyses.…”
Section: Introductionmentioning
confidence: 99%